Charts of highly-ekonomical power SGU with perspective GTU of high-powered - Михайлов, Владимир Евгеньевич; Хоменок, Л. А.; Ермолаев, Павел Андреевич; Кохоновер, Алла Николаевна (Eastern-European Journal of Enterprise Technologies, 2013)
The data are presented for preliminary pre-sketching project of promising power combined-cycle installation (PCI) on the basis of large capacity GT, including GTD-110, manufactured by binary scheme as well as by the schemes of GT auxiliaries. The technical offers are developed for heat and mechanical schemes of powerful generating gas and steam turbines installations with efficiency 62…63%, and also technical request for creation of promising steam and gas turbine installation. The requirements for maneuverability of binary large capacity combined cycle installation are compiled. It is shown that exciting PCI on the basis of GTD-110 and SGT5-2000F (GTE-160) are having efficiency equal to 51…52%. On the basis of promising home-made combined-cycle installation the acquirement of efficiency (brutto) up to 54% is possible (with up-dated GTD-110/GTD-140) and with new licensed GTE SGT5-4000F and up to 60,8% (with future GTD-350). In order to achieve the level of efficiency 62…63% the usage of new technical developments and in particular: increasing of GT efficiency up to 45,2 % the introduction of steam cooling technology, increasing of efficiency of steam loop of binary PCI up to 34…35% and deeper integration of gas and steam turbine cycles.